Jackie Robinson - Hanft, Joshua E (Heinle Reading Library: Biography collection., 2006)
This latest addition to The Heinle Reading Library teaches students the life stories of great American heroes while enhancing reading skills. By providing students with this important foundation, The Heinle Reading Library: Biography Collection offers a unique approach to teaching American culture while expanding fluency.